Association of Group A Streptococcus Exposure and Exacerbations of Chronic Tic Disorders: A Multinational Prospective Cohort Study. (23rd March 2021) - Martino, Davide; Schrag, Anette; Anastasiou, Zacharias; Apter, Alan; Benaroya-Milstein, Noa; Buttiglione, Maura; Cardona, Francesco; Creti, Roberta; Efstratiou, Androulla; Hedderly, Tammy; Heyman, Isobel; Huyser, Chaim; et al.
Abstract : Objective: To examine prospectively the association between group A Streptococcus (GAS) pharyngeal exposures and exacerbations of tics in a large multicenter population of youth with chronic tic disorders (CTD) across Europe. Methods: We followed up 715 children with CTD (age 10.7 ± 2.8 years, 76.8% boys), recruited by 16 specialist clinics from 9 countries, and followed up for 16 months on average. Tic, obsessive-compulsive symptom (OCS), and attention-deficit/hyperactivity disorder (ADHD) severity was assessed during 4-monthly study visits and telephone interviews. GAS exposures were analyzed using 4 possible combinations of measures based on pharyngeal swab and serologic testing. The associations between GAS exposures and tic exacerbations or changes of tic, OC, and ADHD symptom severity were measured, respectively, using multivariate logistic regression plus multiple failure time analyses and mixed effects linear regression. Results: A total of 405 exacerbations occurred in 308 of 715 (43%) participants. The proportion of exacerbations temporally associated with GAS exposure ranged from 5.5% to 12.9%, depending on GAS exposure definition. We did not detect any significant association of any of the 4 GAS exposure definitions with tic exacerbations (odds ratios ranging between 1.006 and 1.235, all p values >0.3). GAS exposures were associated with longitudinal changes of hyperactivity–impulsivity symptom severity ranging from 17% to 21%, depending on GAS exposure definition. Conclusions: This study does not support GAS exposures as contributing factors for tic exacerbations in children with CTD. Specific workup or active management of GAS infections is unlikely to help modify the course of tics in CTD and is therefore not recommended.